Transcriptomic and barrier responses of human airway epithelial cells exposed to cannabis smoke - Aguiar, Jennifer A.; Huff, Ryan D.; Tse, Wayne; Stämpfli, Martin R.; McConkey, Brendan J.; Doxey, Andrew C.; Hirota, Jeremy A. (Physiological reports, 2019)
Globally, many jurisdictions are legalizing or decriminalizing cannabis, creating a potential public health issue that would benefit from experimental evidence to inform policy, government regulations, and user practices. Tobacco smoke exposure science has created a body of knowledge that demonstrates the conclusive negative impacts on respiratory health; similar knowledge remains to be established for cannabis. To address this unmet need, we performed in vitro functional and transcriptomic experiments with a human airway epithelial cell line (Calu‐3) exposed to cannabis smoke, with tobacco smoke as a positive control. Demonstrating the validity of our in vitro model, tobacco smoke induced gene expression profiles that were significantly correlated with gene expression profiles from published tobacco exposure datasets from bronchial brushings and primary human airway epithelial cell cultures. Applying our model to cannabis smoke, we demonstrate that cannabis smoke induced functional and transcriptional responses that overlapped with tobacco smoke. Ontology and pathway analysis revealed that cannabis smoke induced DNA replication and oxidative stress responses. Functionally, cannabis smoke impaired epithelial cell barrier function, antiviral responses, and increased inflammatory mediator production. Our study reveals striking similarities between cannabis and tobacco smoke exposure on impairing barrier function, suppressing antiviral pathways, potentiating of pro‐inflammatory mediators, and inducing oncogenic and oxidative stress gene expression signatures. Collectively our data suggest that cannabis smoke exposure is not innocuous and may possess many of the deleterious properties of tobacco smoke, warranting additional studies to support public policy, government regulations, and user practices. Our study reveals striking similarities between cannabis and tobacco smoke exposure on impairing barrier function, suppressing antiviral pathways, potentiating of pro‐inflammatory mediators, and inducing oncogenic and oxidative stress gene expression signatures. Collectively our data suggest that cannabis smoke exposure is not innocuous and may possess many of the deleterious properties of tobacco smoke, warranting additional studies to support public policy, government regulations, and user practices.